Water pH, not soil pH, alters bacterial community structural pattern and nitrogen cycling pathways in date palm (Phoenix dactylifera L.) roots and bulk soil under freshwater irrigation regime - Sanka Loganathachetti, Dinesh; Mundra, Sunil (Frontiers in Ecology and Evolution, 2023)
Date palms are widely cultivated in arid agroecosystems, where knowledge of irrigation water effect on their soil and root-associated bacterial communities is limited. Using 16S rDNA metabarcoding, we studied soil and root-associated bacterial communities of date palms growing in United Arab Emirates. Overall, 12.18% of bacterial operational taxonomic units (OTUs) were unique to roots, whereas 41.55% were specific to soil. The bacterial diversity was lower in root and community patterns were distinct between compartments, wherein irrigation water pH was a key structuring factor in both compartments, while salinity (electrical conductivity) was important only in the soil. Co-occurrence network analysis revealed a decrease in complexity in the soil-root continuum, and specific taxa/modules also varied with water pH. We observed a higher abundance of endophyte-saprotroph (Bacillus, Streptomyces and Dongia) dual-role OTUs in both compartments, possibly involved in nutrient mobilisation and plant growth. Based on PICRUSt and trait-based analyses, we showed that these OTUs are putatively involved in the nitrogen cycle (nitrification, denitrification, and assimilatory nitrate reduction). Taken together, we suggest that irrigation water pH, not soil pH, transiently affects belowground bacterial communities and selects bacteria in specific pH ranges, which may be important for nutrient cycling (i.e. nitrogen cycle) in arid agroecosystems.